Cuando el Estado te llama: Calidad en los servicios de Cuidado en la primera infancia en la pandemia. Caso del programa JUNTOS - Balbuena Palacios, Patricia (2022)
In Peru, the COVID-19 pandemic has had an impact on various dimensions of human and national development. While it is true that children have not been affected in terms of mortality, there is evidence of a negative impact on their development in the short and long term. In this sense, in Peru, timely and quality care through access to the integrated package of services of the Ministry of Health was severely affected, reducing its coverage and generating risk scenarios for the physical, emotional and mental development of children in the future. In this context, the State promoted temporary interventions through Emergency Decree 095-2020, includin interventions aimed at early childhood development through the National Program of Direct Support to the Poorest “JUNTOS”. This article aims to examine the implementation of these interventions by “JUNTOS”, analyze the challenges and results achieved, and propose working hypotheses for research. It proposes to explain the success of the implementation through: i) innovation in the face of implementation challenges; ii) the relevance of intersectoral coordination; and, iii) improving the quality of public services through universal mechanisms of affiliation and accompaniment to families.